Indocyanine green fluorescence‐guided laparoscopic removal of infected mesh with chronic sinus formation after inguinal mesh plug repair. Issue 1 (8th June 2021) - Shimada, Gen; Hirose, Shuntaro; Matsubara, Taketo; Kishida, Akihiro
Abstract: Chronic mesh infection with sinus formation is usually amenable to open method with dye. Recently, intraoperative real‐time fluorescent imaging has been applied to various organs but not to mesh infection. A 72‐year‐old man with the history of two times removal of infected mesh was referred for groin bulge with purulent discharge. Laparoscopy assisted infected mesh removal was undertaken using intraoperative real‐time fluorescent imaging with indocyanine green injection via the sinus orifice. We experienced the first case of the infected mesh with chronic sinus formation treated by the help of intraoperative indocyanine green fluorescent. This method is simple and easy to apply for laparoscopic assisted removal of chronic mesh infection with sinus.